The effect of ESG score, valuation, and earning on stock price - Muhammad Aliv Alfarizzi; Ike Purnamasari; Zainal Abidin (Kompartemen: Jurnal Ilmiah Akuntansi)
The issue that arises in the minds of potential investors when choosing companies that apply ESG principles and standards in their operational processes creates a trend where investors manage their portfolios with financial assets and shares of companies that have implemented ESG standards in each of their business lines to reduce the risk of corporate uncertainty. The purpose of this study is to empirically demonstrate the effect of ESG Investing, which is projected with ESG Score, valuation, and earnings to the stock price of publicly listed companies on the IDX in 2024. The results show that the three variables tested simultaneously have a positive effect on stock prices with an Adjusted R-Square value of 49.4%, that is 0.494 represents the variation in stock price can be explained by the three independent variables, ESG score, valuation which is represented by P/E Ratio, and earning which is represented by Dividend per Share.